A DFT study of H solubility and diffusion in the Fe-Cr system - Bruzzoni, Pablo (2018)
Density functional theory (DFT) has been used to study the interaction of H with the Fe-Cr system, in particular Fe15Cr. We found that the Cr substitutional atom repeals H; consistently, the H diffusion coefficient is predicted to be reduced in ∼13% with respect to the pure Fe matrix. Moreover, a reduction of approximately one order of magnitude in the H permeation coefficient with respect to pure Fe is also predicted; the result agrees well with experimental data for 9–12% Cr steels and Fe-Cr alloys, and is attributed mainly to solubility effects. As a complementary study, the (absolute) diffusion coefficient of H in pure Fe was evaluated, obtaining good agreement with experimental data and revealing sizable quantum effects in the temperature range of measurements. Highly converged DFT calculations, that kept errors at a feasible minimum, played an essential role in all these results.